Lessons from a systematic tracing process aimed to reduce initial loss to follow-up (ILTFU) among people diagnosed with tuberculosis (TB) in Cape Town, South Africa - Nosivuyile Vanqa; Lario Viljoen; Graeme Hoddinott; Anneke Hesseling; Muhammad Osman; Sue-Ann Meehan (PLoS ONE, 2025)
Background South Africa is a high tuberculosis (TB) burdened country. People who are newly diagnosed with TB must link to a TB treatment facility and be registered in the electronic TB notification system for ongoing care. Delayed linkage to care increases the risk of disease progression, mortality, and ongoing TB transmission. We describe lessons from a systematic tracing process aimed to support linkage to care for people diagnosed with TB. Methods The study used the Western Cape Provincial Health Data Centre (PHDC) to identify persons newly diagnosed with TB (January-December 2020) who were not recorded as linked to care after routine linking efforts, in one peri-urban health sub-district in Cape Town, South Africa. A systematic tracing process was followed, including visits to primary health care (PHC) facilities, and home visits for those with no evidence of linkage at PHC level. Descriptive statistics were used to analyse quantitative data. Lessons learned during the process were documented. Results Within the PHDC, 406 persons diagnosed with TB had no evidence of being linked to TB care. Verification at PHC facilities found that 153/406 (38%) had linked to care. We traced 219 persons; of which107 (49%) could not be found. Overall, the PHDC showed 76% linkage among those traced and found and 72% among those not found. Lessons learned include the need for improved; (i) record keeping enabling the allocation of resources to patients who are truly lost to follow up, (ii) communication to improve patient understanding of timely treatment initiation and (iii) interpersonal relationships to encourage trust. Conclusion The systematic tracing process was useful to understand the complexities around delayed linkage to care. To reduce ILTFU, we recommend, improving accuracy and timely recording of TB data, updating patient contact details regularly and strengthening interpersonal relations and communication between patients and healthcare workers.